APPLICATION OF ESSENTIAL OILS FROM TWO SPECIES OF THE RUTACEAE FAMILY AS CELLULAR OXIDATION CONTROLLER AGENT AND TRYPANOCIDAL CAPACITY - JL, CORREA CALEÑO; Ospina Cc, Cerquera; W, MURILLO ARANGO; JJ, MÉNDEZ ARTEAGA; Perea e, Murillo (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract The essential oil isolated by hydrodistillation from peel of Citrus aurantium and Swinglea glutinosa, collected from Ibagué-Province of Tolima-Colombia (South America), was analyzed by GC/MS. The major compounds identified in essential oil of S. glutinosa were germacrene-D (30.8%), β-pinene (22.6%) and sabinene (11.6%), while limonene (94.4%)was identified as the most abundant component in C. aurantium.The ability of these products and mixturesto control cellular oxidation and measure theiranti-epimastigotes of Trypanosoma cruzi activity, the protozoan Chagas transmitter,were investigated.Besides, the type ofdrug interactionbetweenessential oil mixtureswas determinedby the values ofcombination index, which indicated for all cases the existence of a strong antagonism between the mixtures prepared.According to ABTS assay, β-carotene bleaching test andprotective activityagainst erythrocytes degradationshowed that volatiles compounds have a wide spectrum as cellular oxidation controller.This is the first time, that oils of S. glutinosa and C. aurantium, have high activity against T. cruzi, in vitro; capacity that could be directly associated to the chemotype of they, one of which (Swinglea glutinosa) appears not to be found in other research. Keywords Essential oil composition, Citrusaurantium, Swingleaglutinosa, ABTS, Rutaceae.